2014
DOI: 10.7567/jjap.53.04ep15
|View full text |Cite
|
Sign up to set email alerts
|

Gate oxide reliability on trapezoid-shaped defects and obtuse triangular defects in 4H-SiC epitaxial wafers

Abstract: The reliability of the gate oxide on large-area surface defects (trapezoid-shaped and obtuse triangular defects) in 4H-SiC epitaxial wafers is discussed. Time-dependent dielectric breakdown measurements revealed that a reduction in charge-to-breakdown (Q bd) occurred at a MOS capacitor including the downstream line of those defects. The deterioration of Q bd was at the same level in trapezoid-shaped defects and obtuse triangular defects. A cross-sectional transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…It is further found that all these uneven structures on the epi‐wafer surface cause dielectric breakdowns of the MOS capacitors . Utilization of Berg–Barrett X‐ray topography, TEM, SEM, AFM, and optical microscope allowed us to understand the relationship between “various uneven structures on the epitaxy film surface” and “lattice defects in the epitaxy film resulting in unevenness” . Pits at the dislocation position were regarded as one of the significant factors of the MOS structure dielectric breakdowns on the 8°‐off substrate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is further found that all these uneven structures on the epi‐wafer surface cause dielectric breakdowns of the MOS capacitors . Utilization of Berg–Barrett X‐ray topography, TEM, SEM, AFM, and optical microscope allowed us to understand the relationship between “various uneven structures on the epitaxy film surface” and “lattice defects in the epitaxy film resulting in unevenness” . Pits at the dislocation position were regarded as one of the significant factors of the MOS structure dielectric breakdowns on the 8°‐off substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The cause of occurrence of the epitaxy film surface unevenness is related with the lattice defects in the epitaxy film in many cases. With the basal-plane dislocations with a relatively wide extension that exist in a bare wafer, stepbunchings are formed at the terminal ends on the surface due to the H 2 cleaning process before epitaxy film growth, which in some cases leads to the development of the surface unevenness by the epitaxy film growth process [38,39]. Uneven structures also occur at the terminal ends on the epitaxy film surface of the Frank-type stacking fault (called bar-shaped fault) [39,40].…”
Section: Time-dependent Dielectric Breakdown Of Mos Structure and Dismentioning
confidence: 99%
See 1 more Smart Citation
“…However, the epitaxial growth induces surface waviness due to step bunching, which could significantly degrade the performance of the device. [5][6][7][8][9][10][11] The processing time was 3 min. Figures 6(a)-6(c) show the AFM images obtained over a 2 Â 2 lm 2 area of the pre-processed surface, and the surfaces processed at 2 and 3 min.…”
Section: A)mentioning
confidence: 99%
“…However, the performances of commercially available SiC devices are lower than their theoretical performances, owing to problems such as the non-uniform thickness of the oxide layer and killer defects. [5][6][7][8][9][10][11] One of the reasons for such fundamental problems is the flatness of the SiC substrate. To realize performances equal to the theoretical expectation for SiC devices, an atomically smooth surface without defects must be prepared.…”
mentioning
confidence: 99%